Special Issue "Pediatric Eye Disease: Screening, Causes and Treatment" - Guy L. J. Chen; Jason C. S. Yam; Calvin C. P. Pang (MDPI AG, 2023)
Clinical manifestations and courses of eye diseases in children are profoundly variable, from minor irritations, pain, infections, inflammations, ocular misalignment, refractive errors and visual impairment, to permanent blindness [...]